Profilin as a severe food allergen in allergic patients overexposed to grass pollen. Issue 12 (3rd October 2014) - Alvarado, M. I.; Jimeno, L.; De La Torre, F.; Boissy, P.; Rivas, B.; Lázaro, M. J.; Barber, D.
Abstract Background Profilins are ubiquitous proteins that act as panallergens in sensitized patients, considered to be mild or incomplete food allergens. The aim of the study was to evaluate the role of profilins as severe food allergens in allergic patients overexposed to grass who were referred for severe food reactions and were sensitized to profilins. Methods After a careful in vitro screening, 26 patients were included, classified into two groups, mild (17) and severe reactors (9), based on clinical history and subsequently provoked orally with purified profilin in a double‐blind placebo‐controlled food challenge setup. Results A significant number of patients presented severe positive food challenge test reactions at low doses of the allergen profilin. Patients prone to suffer from severe reactions had lower IgG4/IgE ratio to major grass allergens than those who did not. Conclusion Profilins are complete food allergens in food‐allergic patient populations that are exposed to high levels of grass pollen. This type of patient constitutes an optimal model to understand the link between respiratory and food allergies. The nature of the observed reactions and the low level of allergen eliciting the reactions suggest that intake through the oral mucosa might constitute a relevant route of exposure to food allergens.